Application of Fermented Wheat, Acorns, and Sorghum in Processing of Couscous: Effect on Culinary Quality, Pasting Properties, and Microstructure - Rayene Belmouloud; Hayat Bourekoua; Loucif Chemache; Marcin Mitrus; Leila Benatallah; Renata Różyło; Agnieszka Wójtowicz (Applied Sciences)
This study explores the application of three fermented plant materials—wheat, acorns, and sorghum—in couscous preparation, as well as their impact on its properties. A survey was conducted in some localities in Algeria. The aim is to reproduce the diagrams for the manufacture of different types of couscous incorporated with fermented materials and to evaluate the pasting properties, culinary qualities, and microstructure of each type of couscous produced. The survey identified four couscous formulations made with durum wheat semolina: couscous 1 (4% sorghum, 4% wheat, 8% acorns), couscous 2 (8% acorns), couscous 3 (0.8% sorghum, 6% acorns), and couscous 4 (4% wheat, 4% acorns). A comparative study of the four types of couscous showed significant differences in their physicochemical and microstructural properties. Formulations C3 and C4 showed the best functional performance among all the couscous samples studied. In terms of the swelling index, measured at 25 °C and 95 °C, C3 reached 131.11% and 165.55%, respectively, while C4 recorded 124.9% and 157.0%. Furthermore, these two formulations had the highest viscosity values: initial viscosity of 25 mPas (C3) and 27 mPas (C4), maximum viscosity of 31 mPas (C3) and 30 mPas (C4), and final viscosity of 49 mPas (C3) and 46 mPas (C4). Analysis of the cooking loss revealed higher values for couscous 1 and 2. The microstructure of couscous 2 revealed the presence of native starch particles, open porosity, and a state of partial gelatinization. The study revealed that formulations C3 and C4 significantly (p < 0.05) impact couscous structure by enhancing functionality while preserving quality. It also maintained ancestral knowledge and offered valuable insights for future industrial applications.